14‐3‐3‐β and ‐ε contribute to activation of the osmoprotective transcription factor NFAT5 by increasing its protein abundance and its transactivating activity. Issue 4 (23rd April 2014) - Izumi, Yuichiro; Burg, Maurice B.; Ferraris, Joan D.
Abstract Having previously found that high NaCl causes rapid exit of 14‐3‐3 isoforms from the nucleus, we used siRNA‐mediated knockdown to test whether 14‐3‐3s contribute to the high NaCl‐induced increase in the activity of the osmoprotective transcription factor NFAT5. We find that, when NaCl is elevated, knockdown of 14‐3‐3‐β and/or 14‐3‐3‐ε decreases NFAT5 transcriptional activity, as assayed both by luciferase reporter and by the mRNA abundance of the NFAT5 target genes aldose reductase and the sodium‐ and chloride‐dependent betaine transporter, BGT1. Knockdown of other 14‐3‐3 isoforms does not significantly affect NFAT5 activity. 14‐3‐3‐β and/or 14‐3‐3‐ε do not act by affecting the nuclear localization of NFAT5, but by at least two other mechanisms: (1) 14‐3‐3‐β and 14‐3‐3‐ε increase protein abundance of NFAT5 and (2) they increase NFAT5 transactivating activity. When NaCl is elevated, knockdown of 14‐3‐3‐β and/or 14‐3‐3‐ε reduces the protein abundance of NFAT5, as measured by Western blot, without affecting the level of NFAT5 mRNA, and the knockdown also decreases NFAT5 transactivating activity, as measured by luciferase reporter. The 14‐3‐3s increase NFAT5 protein, not by increasing its translation, but by decreasing the rate at which it is degraded, as measured by cycloheximide chase. It is not clear at this point whether the 14‐3‐3s affect NFAT5 directly or indirectly through their effects on other proteins that signal activation of NFAT5.